1990
DOI: 10.1063/1.459084
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and diffusion of a Lennard-Jones vapor in microporous silica

Abstract: The properties of a dilute Lennard-Jones vapor in contact with an adsorbing microporous medium are investigated using grand canonical ensemble Monte Carlo and molecular dynamics techniques. The bulk structure of the microporous system is modeled as an assembly of randomly distributed interconnected solid spheres, and vapor/surface interactions are treated in two ways: (i) using a smooth continuous interaction potential and (ii) using a molecular model for the surface structure of the solid. The microporous sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 63 publications
3
69
0
1
Order By: Relevance
“…Nitrogen adsorption has been a useful method in characterizing the nanoporous materials for pore size distribution [12,13] and SSA estimation [14] and there is plenty of experimental data for comparison. MacElroy [15] studied properties of methane, such as the Henry constant, in microporous silica with a random micro-sphere system and vitreous state sphere structure, and found results in satisfactory agreement with experimental data, and concluded that with a proper microsphere structure the numerical method could give a reasonable prediction on properties of simple nonpolar gases in silica aerogels. Ulker [16] simulated a nitrogen adsorption isotherm in silica aerogel MOF composite with conventional GCMC and it agrees with the experimental data.…”
Section: Introductionsupporting
confidence: 49%
“…Nitrogen adsorption has been a useful method in characterizing the nanoporous materials for pore size distribution [12,13] and SSA estimation [14] and there is plenty of experimental data for comparison. MacElroy [15] studied properties of methane, such as the Henry constant, in microporous silica with a random micro-sphere system and vitreous state sphere structure, and found results in satisfactory agreement with experimental data, and concluded that with a proper microsphere structure the numerical method could give a reasonable prediction on properties of simple nonpolar gases in silica aerogels. Ulker [16] simulated a nitrogen adsorption isotherm in silica aerogel MOF composite with conventional GCMC and it agrees with the experimental data.…”
Section: Introductionsupporting
confidence: 49%
“…It has already been shown that this model is a reasonable first approximation to the structure of silica gel [12].…”
Section: Model Descriptionmentioning
confidence: 99%
“…MacElroy and Raghavan [27] studied dilute Lennard-Jones (LJ) vapor confined in microporous silica modelled in two ways as a network of randomly interconnected, and randomly distributed silica microparticles. Kaminsky and Monson [28,29] developed a model for adsorption of LJ fluid in microporous silica gel comprising a configuration of microspheres, each considered as a continuum of atomic interaction centers.…”
Section: Introductionmentioning
confidence: 99%
“…The aerogel is modelled as a network of partially overlapping compact carbon nanospheres. To illustrate the effect of the aerogel nanostructure, it is represented by two models which are reminiscent of those used by MacElroy and Raghavan [27]: nanospheres that are almost randomly distributed, and nanospheres associating into a network of branched chains. As shown below, the long-range correlations of aerogel nanoparticles strongly affect the structure and thermochemistry of the EDL formed by the sorbed electrolyte solution at the surface of carbon aerogel nanopores.…”
Section: Introductionmentioning
confidence: 99%